EVALUASI SKENARIO MANAJEMEN LALU LINTAS PADA U-TURN JALAN TEUKU UMAR DENGAN METODE ANALYTIC HIERARCHY PROCESS - Michael; Salsabila, Laira; Khanza, Ayu Kamila (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
Jalan Teuku Umar is main road segment in Bandar Lampung city that has a crucial role to support the mobility and economic activity. However, high traffic volume and U-Turn existence can contribute to traffic jam which may decrease the performance of the traffic. This study aims to evaluate the traffic management scenarios, which can be applied on Jalan Teuku Umar, using Analytic Hierarchy Process method. The evaluation can be a consideration for policy making in traffic management. Furthermore, the scenarios that is evaluated in this study are U-Turn closing, U-Turn N-S and S-N relocating to 30 m to north and 40 m to south, respectively, and U-Turn S-N relocating 195 m to north. Those scenarios are compiled from the latest study using microsimulation approach. The study is conducted using 6 (six) criteria, which consist of traffic performance, cost, comfort, saety, environment impact and social impact. The survey involves several experts to respond the questionnaire. The results show that traffic performance is dominant criteria and the third scenario, which relocating U-Turn S-N 195 m to north, is chosen as the most appropriate management scenario for the U-Turn. The study is expected to be a reference for local government to formulate the policy related traffic management, hence the traffic system becomes more effective, efficient and sustainable.